Diverse and healthy cropping systems trial protocol - Kumar, Sunil; Choudhary, Kajod Mal; Gathala, Mahesh Kumar; Mohanty, Samarendu; Kakraliya, S.; Rout, Bidhyadhar; Kishore, Avinash; Gupta, Manavi; Patwardhan, Sharvari; Neupane, Sumanta; Sinha, Pooja; Jat, Raj Kumar (International Maize and Wheat Improvement Center, 2022)
On-Farm Research Trials are part of TAFSSA’s Work Package 2 (WP2) activities. WP2 emphasizes farm-and landscape-level interdisciplinary research to identify strategies to increase farmers’ profits and nutritional yields, conserve resources, and maintain or enhance ecological services, while also mitigating greenhouse gas (GHG) emissions from farms and agricultural landscapes. Going beyond typical agriculture-nutrition programs in South Asia we explore field-and landscape-scale crop and animal farm diversification options supporting multiple benefits, including potential nutritional yield, across environmental and socioeconomic gradients of rice and maize-based farming systems. Nalanda district of Bihar in eastern India has been selected as a learning site based on key information on food and nutrition security gaps, environmental stresses and climate challenges as well as the prevalence of commodities and farming systems that offer the greatest potential to achieve TAFSSA’s outcomes.